Correction: Separating extracellular vesicles and lipoproteins via acoustofluidics. Issue 18 (19th August 2020) - Wu, Mengxi; Chen, Chuyi; Wang, Zeyu; Bachman, Hunter; Ouyang, Yingshi; Huang, Po-Hsun; Sadovsky, Yoel; Huang, Tony Jun
Abstract : Correction for 'Separating extracellular vesicles and lipoproteins via acoustofluidics' by Mengxi Wu et al., Lab Chip, 2019, 19, 1174–1182, DOI: ; 10.1039/C8LC01134F .